Покращення показників України у досягненні цілей сталого розвитку ООН - Сербенюк, С. О.; Serbenyuk, S. O. (Вісник Харківського національного університету внутрішніх справ. – 2024. – № 1 (104), ч. 1. - С. 44-52, 2024)
Статтю присвячено формулюванню спрощеного переліку вимог до закладів вищої освіти, що висуваються провідними рейтинговими агенціями для включення в міжнародні рейтинги щодо діяльності в контексті сталого розвитку. Виконання відповідних вимог стосовно діяльності та нормативної бази ЗВО створює умови для захисту екології, розвитку економіки, укріплення правової держави. Додатково представлено фрагментарний історичний огляд розвитку сучасного змісту поняття «сталий розвиток» та української нормативної правової бази щодо Цілей сталого розвитку.

The research is devoted to the formulation of a simplified list of requirements for higher education institutions put forward by leading rating agencies for inclusion in international rankings of activities in the framework of sustainable development. Compliance with the relevant requirements for the activities and regulatory framework of higher education institutions creates conditions for increasing the number of Ukrainian institutions in international rankings, improving the position of existing higher education institutions, as well as for improving the image of our country in the international arena, attracting investment and increasing the efficiency of recovery (reconstruction), strengthening Ukraine as a state governed by the rule of law, protecting the environment, and developing the economy. In addition, a fragmentary historical overview of the modern content of the concept of “sustainable development” and the Ukrainian regulatory framework for the Sustainable Development Goals is presented. Despite the great attention of the global and Ukrainian scientific community to the activities of higher education institutions in the context of sustainable development, many studies are general in nature, detailing such activities and their specifics in the context of one or more of the UN Sustainable Development Goals, or are fragmentary. Moreover, there is no clear, coherent, simplified list of the necessary requirements for the activities and regulatory framework of higher education institutions that would meet the criteria of good practice at various levels. The impact of sustainable development activities of universities on the growth of the state's image in the international arena and the attraction of additional allocations for economic reconstruction, as well as on strengthening the rule of law, requires more detailed research. The recommendations for higher education institutions contribute to: restoration of ecology and prevention of environmental crimes and offences; creation of conditions for social security and a “safe society” environment, increase of employees’ motivation on the basis of fair remuneration, ensuring rights and freedoms; improvement and qualitative impact on the development of social relations as a result of cooperation of higher education institutions with authorities (local, regional, national), local residents, business, volunteers, as well as international enterprises; attracting investment, including foreign investment, based on quality management, fair cooperation, environmental culture, compliance with the law, including international law; sustainable development of communities and economic relations based on the previous points; strengthening the institution of the Ombudsman, improving the international image of Ukraine in terms of respect for rights and freedoms, business opportunities, including investment.

Статья посвящена формулированию упрощенного перечня требований к учреждениям высшего образования, выдвигаемым ведущими рейтинговыми агентствами для включения в международные рейтинги по деятельности в контексте устойчивого развития. Выполнение соответствующих требований по деятельности и нормативной базе ЗВО создает условия для защиты экологии, развития экономики, укрепления правового государства. Дополнительно представлен фрагментарный исторический обзор развития современного содержания понятия «устойчивое развитие» и нормативной правовой базы относительно Целей устойчивого развития.
Improving Ukraine’s progress in achieving the UN Sustainable Development Goals
Keywords: заклади вищої освіти; Цілі сталого розвитку ООН; економічна стійкість; нормативно-правова база; Україна; institutions of higher education; UN Sustainable Development Goals; economic stability; legal framework; Ukraine; заведения высшего образования; Цели устойчивого развития ООН; экономическая устойчивость; нормативно-правовая база; Украина